Foreign Direct Investment and export performance: The Peruvian experience in the framework of APEC (Journal of Business, Universidad del Pacífico (Lima, Peru), 2016)
This research measures the impact of APEC economies FDI on Peru's total exports. Solving this question will help us understand the effect that this FDI has on the Peruvian economy through its export capacity, as well as determine whether or not this FDI stimulates an export-oriented industrialization. Using data from  Proinversion, Ministry of Foreign Trade and Tourism (MINCETUR), Central Reserve Bank, SUNAT, the World Bank and StatsAPEC we developed an ordinary least squares (OLS) model  and observed that APEC economies FDI has a positive effect on exports. Specifically, an increase in 1 million soles of APEC FDI generates an increase of 44.37 million soles in exports. However, this positive effect has a decreasing marginal returrn as the investment stock rises.